Clinical researchThe use of whey protein concentrate in management of chronic hepatitis C virus – a pilot study - Elattar, Gamal; Saleh, Zeinab; EL-Shebini, Safinaz; Farrag, Atif; Zoheiry, Mona; Hassanein, Azza; EL-Ghannam, Maged; Shendy, Shendy; EL-Dabaa, Ehab; Zahran, Nariman (Archives of Medical Science, 2010)
Introduction : Whey protein contains biologically active ingredients that can prevent and attenuate disease besides being nutritive. The aim of the study was to clarify the effects of oral administration of whey protein on viral load and host defence mechanisms, in particular, phagocytic function of neutrophils, selected immunomodulatory cytokines and serum inflammatory markers, in compensated chronic hepatitis C virus (HCV) patients. Material and methods : Twenty-seven HCV patients (20 males and 7 females) recruited from the hepatology clinic of the Theodor Bilharz Research Institute (TBRI) were given whey protein concentrate (WPC) twice daily for two months. In addition, 15 age and sex matched healthy participants were included in the study, as a control group. Neutrophil phagocytic activity, serum intercellular adhesion molecule (sICAM), interleukin-2 (IL-2), nitric oxide (NO), as well as HCV-RNA levels and routine investigations were determined for patients, before and after WPC supplementation and once for the control group. Results : There was a significant decrease in viral load and markers of active inflammation, alanine aminotransferase (ALT) and aspartate aminotransferase (AST), while serum albumin, total leucocyte counts and absolute neutrophil counts showed significant elevation accompanied by improvement of neutrophil phagocytic activity after WPC supplementation compared to pre-treated levels. The oral WPC supplementation was well tolerated without any serious adverse events. Conclusions : Oral supplementation of WPC has promising results as a new therapeutic strategy against HCV and its sequelae by decreasing the viral load and active inflammation as well as improving the synthetic capacity of the liver and the phagocytic function of neutrophils, in these patients.